Tourist Boat Electrification - Hendro Agus Widodo; Joesianto Eko Poetro; M. Basuki Rahmat; Purwidi Asri; Edy Prasetya H; Catur Rahmat H (LPPM of NAROTAMA UNIVERSITY, 2021)
As a city crossed by rivers, Surabaya has the potential for attractive water tourism. Kalimas is one of them. Kalimas is a river that divides Surabaya. Kali Mas is a tributary of the Brantas River. This main river flows from Mojokerto as its headwaters, then flows to the northeast, empties into Surabaya, and ends in the Madura Strait. Muara Kali Mas has been Surabaya's traditional port for centuries. This port became the gateway to the capital of the Majapahit Kingdom (in Trowulan), and became part of the Surabaya people's battle against the allies before November 10, 1945. In various countries, river tourism has developed. Not only for city residents, but has become part of the State's tourism. One example is in Italy, namely tracing the river canals in Venice in Italy. Everything is described so well that everyone who comes wants to try it. Experiences and interesting photo documentation make river tourism an opportunity to develop. River tourism can be a potential alternative for Surabaya residents. Become a means of recreation or further developed into a tourist vehicle of national and even international standards. An important means of water tourism is a boat. Tour boats were developed to support the success of this tour. This article discusses the electrical installation for tourist boats that will be used on the Kali Mas River. Its power source is taken from diesel engines and also from solar panels that are capable of generating electricity.